Study of Liquid Organic Fertilizer Application with Empty Palm Oil Bunch Ash Nano on Soyabean (Glycine max L.) - Gatot Supangkat Samidjo; Mulyono Mulyono; Bambang Isnawan; Henny Febriani; Ngafwan Ngafwan (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Proper fertilization is an effort to increase soybean production. This study aimed to examine the effect of Liquid Organic Fertilizer (LOF) application enriched with Empty Palm Oil Bunch (EPOB) Ash Nano and determine the optimal concentration on soybean growth and yield. This research was carried out at the Experimental Field of the Faculty of Agriculture, Universitas Muhammadiyah Yogyakarta. This research was conducted using a single factor experimental method which was arranged in a Completely Randomized Design. The treatments tested were rabbit urine LOF; Rabbit urine LOF + EPOB Ash Nano 1%; Rabbit urine LOF + EPOB Ash Nano 2%; Rabbit urine LOF + EPOB Ash Nano 3% and rabbit urine LOF + EPOB Ash Nano 4%. The results showed that the application of rabbit urine LOF + EPOB Ash Nano 4% could increase soybean growth and was able to increase the dry weight of 100 seeds. Application of rabbit urine LOF enriched with EPOB Ash Nano can save nitrogen nutrient fulfillment for soybeans by up to half the recommended dose.